2005
DOI: 10.1002/cncr.21159
|View full text |Cite
|
Sign up to set email alerts
|

Loss of carcinoembryonic antigen‐related cell adhesion molecule 1 expression is an adverse prognostic factor in hepatocellular carcinoma

Abstract: BACKGROUNDCarcinoembryonic antigen‐related cell adhesion molecule 1 (CEACAM1) is a negative regulator of tumor cell growth, and may function as a tumor suppressor. CEACAM1 expression is down‐regulated with increasing histologic grade in a number of malignancies. The authors hypothesized that loss of CEACAM1 expression in hepatocellular carcinoma (HCC) cells may function as an adverse prognostic factor.METHODSA retrospective analysis was conducted of 139 consecutive patients who underwent resection for HCC, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…The CEACAM1 protein expression levels in primary OSCCs were significantly associated with tumor size (p = 0.022). In hepatocellular carcinomas, a clinical study also reported that decreased CEACAM1 expression was correlated with larger tumors [41], which was consistent with the results obtained in this study. Moreover, the status of the protein CEACAM1 expression differed significantly between the early stages (I and II) and the advanced stages (III and IV; Mann-Whitney U test; p < 0.001).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The CEACAM1 protein expression levels in primary OSCCs were significantly associated with tumor size (p = 0.022). In hepatocellular carcinomas, a clinical study also reported that decreased CEACAM1 expression was correlated with larger tumors [41], which was consistent with the results obtained in this study. Moreover, the status of the protein CEACAM1 expression differed significantly between the early stages (I and II) and the advanced stages (III and IV; Mann-Whitney U test; p < 0.001).…”
Section: Discussionsupporting
confidence: 83%
“…Decreased expression of CEACAM1 has been reported in many malignant tumors of the breast [33], colon [34], endometrium [35], prostate [36,37,38], bladder [39] and liver [40, 41]. Based on these results, we postulated that CEACAM1 may have a tumor-suppressive role.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Studies have shown that CEACAM1 expression in colon, hepatoma and prostate cancers can inhibit tumor growth. Loss of gene expression or downregulation has been frequently observed, indicating that it may act as a tumor suppressor [4-8]. CEACAM1 overexpression in thyroid and non-small cell cancer and melanomas are often associated with poor clinical outcome and poor survival [8-11].…”
Section: Introductionmentioning
confidence: 99%
“…The decision to use neoadjuvant chemotherapy was made by the Institutional Cancer Committee of Niigata University Medical and Dental Hospital. Indications for neoadjuvant chemotherapy included multiple hepatic tumors or a solitary tumor >3 cm in diameter, because these preoperative factors are closely associated with vascular invasion or poor post-resection survival (15)(16)(17). In the current series, 16 patients received neoadjuvant chemotherapy, which consisted of hepatic arterial infusion of a fine-powder formulation of cisplatin (IA-call ® , Nippon Kayaku, Co., Ltd., Tokyo, Japan; recommended dose of 65 mg/m 2 ) under the guidance of hepatic angiography.…”
Section: Patient Population From March 2007 Through Decembermentioning
confidence: 99%